Pendidikan Akhlak Dalam Kitab Bugyah Al-??lib Karya Syaikh ‘Abdull?h Al-Harar? - Khairuddin Khairuddin; Azizah Hanum; Junaidi Arsyad (Dinasti Review, 2024)
This study aims to analyse the biography of Shaykh 'Abdull?h Al-Harar? and the characteristics of Bugyah Al-??lib, to analyse the concept of Shaykh 'Abdull?h Al-Harar? regarding moral education and its division contained in Bugyah Al-??lib, and analysing the relevance of moral education in the book Bugyah Al-??lib by Shaykh 'Abdull?h Al-Harar? with moral education today. This research uses the library research method. Data analysis in this study was carried out using data analysis techniques with content analysis, namely: studying, examining and analysing the book Bugyah Al-??lib by Shaykh 'Abdull?h Al-Harar? recording the material in the form of a summary, looking for other references and collecting things related to the research, matching with relevant books, analysing the reading sources more deeply and drawing conclusions from the results of the research. The results of this study tell us that there are many moral education materials that must be owned by all humans, especially for a teacher and student of Islamic Education. All of these materials are contained in the book Bugyah Al-??lib by Shaykh 'Abdull?h Al-Harar?. The material consists of praiseworthy morals which are poured in the chapter on the obligations of the heart, disgraceful morals in the chapter on the sins of the heart, and 7 sins of the limbs consisting of the sin of the stomach, the sin of the eyes, the sin of the tongue, the sin of the ears, the sin of the hands, the sin of the farji, the sin of the feet, and the sin of the body. The purpose of Shaykh 'Abdull?h Al-Harar? writing this book is so that all people can easily learn religious knowledge, which is Fardlu 'Ain for every mukallaf. So that Islamic religious knowledge can be distributed easily and accepted by various groups of society, especially Islamic education.